Differences between offensive and defensive ratings of rookies and sophomores in the NBA basketball league - Prieto, J. (Cuadernos de Psicología del Deporte, 2017)
The purpose of this study was to analyse and compare the offensive and defensive performance of rookies (first-year players) and sophomores (second-year players) in the NBA basketball league, in order to ascertain whether a second year of experience in the league results in higher performances. We hypothesised to find overall higher offensive and defensive performances in second-year players when compared to first-year. Oenffsive and defensive rating statistics for rookies and sophomores for seasons 2014/2015 and 2015/2016 were downloaded and filtered from the stats section of the NBA ocial web portal for a total of 144 players under analysis. A multivariate analysis of covariance (MANCOVA) was computed. ‘Offensive Rating’ and ‘Defensive Rating’ were used as dependent variables; ‘Level of Experience’ (rookie vs. sophomore) was used as independent variable. The average number of minutes played by each player during the league was considered as a covariate. Contrary to what was hypothesised, although both offensive and defensive ratings showed slightly higher values for second-year players when compared to first-year players, the differences were not statistically significant. These results suggest that one more year of experience in the league is not sufficient to signicantly increase the performance of the players on their way from rookies to sophomores. Hence, the results might suggest that the road to excellence has begun to be travelled, with two seasons in the league still being insufficient to show significant differences in the overall performance of these yet novice players.